The Influence of Macroeconomic Conditions on Export Performance in the ASEAN Region from 2017 to 2024 - Syifa Arifatul Maula; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the influence of macroeconomic conditions on export performance in the ASEAN region for the period 2017-2024, taking into account the variables Gross Domestic Product (GDP), exchange rate, and inflation. The research employs a descriptive quantitative approach with panel data analysis. Quantitative analysis is conducted using panel data regression techniques to examine the relationship between the dependent variable, namely export volume, and the independent variables, namely GDP, exchange rate, and inflation. The results show that GDP has a positive and significant effect on export volume, while the exchange rate has a negative but significant effect. Inflation, although included as an independent variable, does not show a significant influence on export volume. These findings indicate that GDP and the exchange rate are key factors affecting export performance in the ASEAN region, while inflation does not play an individual role within the examined period.